The Evaluation of the Genre Ceria Program in Jakarta Using the CIPP Evaluation Model - Dewi Kartika Sari; Khaerul Umam Noer; Evi Satispi; Retnowati WD Tuti (Budapest International Research and Critics University, 2022)
This paper focuses on evaluating the Generasi Berencana (GenRe Ceria) program, particularly on access to reproductive health, which is carried out by the National Population and Family Planning Agency of DKI Jakarta Province, which targets girls as policy subjects. BKKBN data mentions 57,688,472 people in the adolescent age range, meaning that one out of every four people in Indonesia is a teenager. This considerable amount is a potential that requires a planned, systematic, and structured management to benefit the nation's development capital in the future. The Ceria genre began in 2015 and ended in 2020, with an approach to youth by developing the Youth/Student Information and Counseling Center (Pusat Informasi dan Konseling Remaja/Mahasiswa/PIK R/M) in schools. This paper aims to evaluate the Generation Planning program in DKI Jakarta using the CIPP Evaluation Model on PIK R/M in six schools in DKI Jakarta Barat, spearheading efforts to provide access to reproductive health services and information for adolescent girls. By using qualitative research methods, this paper argues that the Ceria Genre program runs optimally even though it tends to focus on teenagers in school, ignores teenagers who drop out of school, and the inability to understand the cultural situation of the community.